Unraveling the complexity of follicular fluid: insights into its composition, function, and clinical implications - Yurong Pan; Chenyu Pan; Chunping Zhang (BMC, 2024)
Abstract Follicular fluid (FF) plays a vital role in the bidirectional communication between oocytes and granulosa cells (GCs), regulating and promoting oocyte growth and development. This fluid constitutes a complex microenvironment, rich in various molecules including hormones, growth factors, cytokines, lipids, proteins, and extracellular vesicles. Understanding the composition and metabolic profile of follicular fluid is important for investigating ovarian pathologies such as polycystic ovary syndrome (PCOS) and endometriosis. Additionally, analyzing follicular fluid can offer valuable insights into oocyte quality, aiding in optimal oocyte selection for in vitro fertilization (IVF). This review provides an overview of follicular fluid composition, classification of its components and discusses the influential components of oocyte development. It also highlights the role of follicular fluid in the pathogenesis and diagnosis of ovarian diseases, along with potential follicular fluid biomarkers for assessing oocyte quality. By understanding the intricate relationship between follicular fluid and oocyte development, we can advance fertility research and improve clinical outcomes for infertility patients.